ANALISIS JARINGAN LGBT DI KOTA MAKASSAR MENGGUNAKAN BLUED DAN TWITTER: SOCIAL NETWORK ANALYSIS (SNA): ANALISIS JARINGAN LGBT DI KOTA MAKASSAR MENGGUNAKAN BLUED DAN TWITTER: SOCIAL NETWORK ANALYSIS (SNA) - Kurniawan; Tuti Bahfiarti; Muliadi Mau; Wahyuddin (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2024)
LGBT issues have become a global conversation, spreading through a series of pro-LGBT movements that have been around for a long time. This study aims and focuses on analyzing the communication network of LGBT people in Makassar City by using the Blued application and its connection through Twitter. This study uses the interpretative phenomenological analysis (IPA) approach to see the conditions in the field and uses social network analysis (SNA) to see the relationships generated in Blued social media and Twitter about LGBT using the keywords LGBT Makassar, Gay Makassar, Blued Makassar. The use of this approach is expected to be able to explore and examine more deeply about LGBT, especially in Makassar City through Twitter and the Blued application. The results of the research using Blued as a live streaming and entertainment media are the same as its peers such as Tiktok and Bigo Live, but Blued is more intended for LGBT people where they can chat via chat, live broadcast, and others, there are even rankings and celebrity levels in the application, while social network analysis shows nodes 253, edges 345, degree 1. 364, diameter 2, average path length 1.295. while degree centrality analysis 61, betweenness centrality 0.000435, 1.0, eigenvector centrality 1.0. Keywords: Network Analysis, LGBT, Blued, Twitter, Social Network Analysis